Tailoring Hydrothermal Vent Biodiversity Toward Improved Biodiscovery Using a Novel in situ Enrichment Strategy - Stokke, Runar; Reeves, Eoghan P.; Dahle, Håkon; Fedøy, Anita-Elin; Viflot, Thomas; Lie Onstad, Solveig; Vulcano, Francesca; Pedersen, Rolf B.; Eijsink, Vincent G. H.; Steen, Ida H. (Frontiers in Microbiology, 2020)
Deep-sea hydrothermal vents are amongst the most extreme environments on Earth and represent interesting targets for marine bioprospecting and biodiscovery. The microbial communities in hydrothermal vents are often dominated by chemolitoautotrophs utilizing simple chemical compounds, though the full extent of their heterotrophic abilities is still being explored. In the bioprocessing industry, where degradation of complex organic materials often is a major challenge, new microbial solutions are heavily needed. To meet these needs, we have developed novel in-situ incubators and tested if deployment of recalcitrant materials from fish farming and wood-pulping industries introduced changes in the microbial community structure in hot marine hydrothermal sediments. The incubation chambers were deployed in sediments at the Bruse vent site located within the Jan Mayen vent field for one year, after which the microbial populations in the chambers were profiled by 16S rRNA Ion Torrent amplicon sequencing. A total of 921 operational taxonomic units (OTUs) were assigned into 74 different phyla where differences in community structure were observed depending on the incubated material, chamber depth below the sea floor and/or temperature. A high fraction of putative heterotrophic microbial lineages related to cultivated members within the Thermotogales were observed. However, considerable fractions of previously uncultivated and novel Thermotogales and Bacteroidetes were also identified. Moreover, several novel lineages (e.g members within the DPANN superphylum, unidentified archaeal lineages, unclassified Thermoplasmatales and Candidatus division BRC-1 bacterium) of as-yet uncultivated thermophilic archaea and bacteria were identified. Overall, our data illustrate that amendment of hydrothermal vent communities by in-situ incubation of biomass induces shifts in community structure towards increased fractions of heterotrophic microorganisms. The technologies utilized here could aid in subsequent metagenomics-based enzyme discovery for diverse industries.